1997
DOI: 10.1016/s0925-4439(97)00083-5
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of glycosaminoglycans by reactive oxygen species derived from stimulated polymorphonuclear leukocytes

Abstract: The effect of reactive oxygen species (ROS), generated by in vitro stimulation of isolated PMN upon the main GAG components of mineralised and non-mineralised connective tissues was investigated. PMN were isolated from whole blood and the production of the ROS superoxide (O2.-) and hydroxyl radicals (.OH) was stimulated by the addition of phorbol myristyl acetate (PMA) and PMA/FeCl3-EDTA chelate respectively and their production assessed over a 24 h period. The glycosaminoglycans (GAG), hyaluronan, chondroitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
102
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 35 publications
7
102
0
2
Order By: Relevance
“…Sulfur is a component of proteoglycans (chondroitin sulfate and keratan sulfate), and changes in their levels indicate damage to the organic dentin matrix. [38][39][40] These changes in proteoglycans might interfere in the maintenance of interfibrillar spaces, 41 which may have compromised diffusion of the adhesive into the collagen network, potentially reducing the bond strength in this current study. 42,43 The specimens from group C (Figure 3) presented a thick hybrid layer þ resin tags and also high microtensile bond strength values.…”
Section: Discussionmentioning
confidence: 93%
“…Sulfur is a component of proteoglycans (chondroitin sulfate and keratan sulfate), and changes in their levels indicate damage to the organic dentin matrix. [38][39][40] These changes in proteoglycans might interfere in the maintenance of interfibrillar spaces, 41 which may have compromised diffusion of the adhesive into the collagen network, potentially reducing the bond strength in this current study. 42,43 The specimens from group C (Figure 3) presented a thick hybrid layer þ resin tags and also high microtensile bond strength values.…”
Section: Discussionmentioning
confidence: 93%
“…[29][30][31] In vitro studies have shown that inflammatory cytokines, particularly IL-1, IL-6, and TNF-a, as well as reactive oxygen species are involved in the degradation of HA. [32][33][34] High serum levels of HA have been reported in CKD [35][36][37] and seem to be a risk predictor of poor survival in dialysis. 38 However, the mechanisms underlying the increased levels have not been fully explained.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence implicate polymorphonuclear cells (PMNs) as the primary mediators of the host response against periodontopathic bacteria (Miller et al 1984). A study carried out by Moseley et al (Moseley et al 1997) demonstrates that PMNs produce a range of antimicrobial factors, including ROS, during the phagocytosis of periodontopathic bacteria. ROS have recently been reviewed in the pathogenesis of periodontitis (Canakci et al 2005).…”
Section: Introductionmentioning
confidence: 99%